Quality control issues for the roads of LGED; present state, challenges and scope of improvement - Islam, Md. Fatemul (BRAC Univeristy, 2017)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2017.